Second order observations on a coaching programme: the changes in organisational culture - Geraint Evans (International Journal of Evidence Based Coaching and Mentoring, 2011)
The purpose of this study is to illuminate the relationship between a coaching programme and the consequent changes within a scientific services unit of a UK county police force, using organisational culture as the lens to view and interpret the outcomes. A qualitative case study is used to create a detailed description of the changes in behaviour of managers and SSU staff and the consequent shift in the organisation climate, practice and culture. The findings suggest that management behaviour influences the organisational climate and contributed to an environment that changed the way members of the SSU related to each other and the divisional aims. Furthermore, the study highlighted individual sense-making of the coaching programme and the outcomes and surfaced the paradox of using person-centred non-directive coaching for explicit directed organisational change.